Implementing lean manufacturing in small and medium scale enterprises-identification and modelling of managerial factors. (2016) - Ramadas, T.; Satish, K.P.; Ramkumar, P.N.
The aim of this research paper is to present the managerial factors that constitutes a successful implementation of lean manufacturing within the small and medium scale enterprises (SMEs). Lean manufacturing concepts not only reduce the cost of production, but also reduce the number of defects. For this purpose, shop floor commitment and employee trust, business strategy based on customer demand, analysis of data, linking lean into the business were labelled as four construct with 19 variables to measure the managerial factor. Empirical data was collected to measure these managerial contributing factors in different industries in Kerala, India. A structural equation modelling (SEM) was used build up the measurement model. This is the first known study that adopts SEM framework to measure the managerial contributing factors towards the success of lean implementation. After the analyses of the results, shows that these four construct with 14 variables are significant to the managerial involvement.